Degradation of concrete in marine environment under coupled chloride and sulfate attack: A numerical and experimental study - Dandan Sun; Zhenjie Cao; Changfu Huang; Kai Wu; Geert De Schutter; Lihai Zhang (Case Studies in Construction Materials, 2022)
The corrosion of offshore reinforced concrete structures under combined chloride and sulfate ions attack is a complex corrosion phenomenon. The purpose of this study is to develop numerical models in conjunction with experimental studies for long-term durability assessment of offshore concrete structures. A numerical model was developed to describe the simultaneously transport of chloride and sulfate ions considering the competitive binding by hardened cement pastes effect. The model was validated by a series of experimental studies. The validated model was implemented to predict the service life of the offshore RC structures under various chloride and sulfate solutions. The results show that chloride ions induced corrosion of steel bars in offshore RC structures is highly influenced by the concentration of sulfate ions. The sulfate ions induced concrete expansion and cracking from ettringite formation could potentially accelerate chloride ions induced corrosion of steel bars in concrete, ultimately the premature failure of the offshore RC structures.